Analisis Nilai Perusahaan Property Dan Real Estate Bursa Efek Indonesia - LItausiil Rizqi; Muhadjir Anwar (LPPM Universitas Sains dan Teknologi Komputer, 2021)
The firm value can be interpreted as a measure of the success of the firm’s performance in increasing the prosperity of shareholders. The purpose of this study to determine the effect of profitability and capital structure on the firm value and the role of the capital structure as an mediating variable in property and real estate companies listed on the Indonesia Stock Exchange period 2017-2019. The sampling techniques in this study using purposive sampling technique with total sample of 44 companies. The analysis technique used is path analysis. This study finds the results that profitability has a significant positive effect on firm value, profitability has a significant positive on capital structure, capital structure has a non significant effect on firm value, and capital structure is not able to mediate the effect of profitability on firm value of property and real estate.